Homogeneous and Hybrid Girder Design in the 1969 AISC Specification - Milek, Jr. (Engineering Journal, 1970)
The rules for design of plate girders in the 1969 AISC Specification are basically unchanged from the 1963 edition, except that a highly significant extension has been made to provide for the design of hybrid beams. In addition, Section 1.10 has been editorially revised to increase clarity of intent. The principal formulas governing girder design are unchanged, but the designer now has the option of achieving an economical design by either of two concepts: (1) tension field action in the thin web of a homogeneous girder, or (2) hybrid design using a low strength steel web plate welded to high strength steel flanges.